UJI EFEK EKSTRAK N-HEKSAN DAUN BAWANG KUCAI (Allium Tuberosum Rottl . Ex Spreng) TERHADAP KADAR KOLESTEROL DALAM LDL (Low Density Lipoprotein) PADA TIKUS PUTIH (Rattus Norvegicus) JANTAN GALUR WISTAR - ., Wan Hesti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Garlic chives/kucai ( Allium TuberosumRottl ExSpreng) contain Allicin that has an inhibitory effect for HMG-KOAreductase enzyme resulting in decreased cholesterol level.Objective: the research would investigate the effect of reductionLDL (Low Density Lipoprotein) and effective dose of garlic chivessn-hexane extract in male wistar rate compared with pravastatin asposstive control. Method: the research was a time seriesexperiment. Twenty five wistar rat was randomly divided into 5experimental group, negative control ( CMC 1% ), positive control pravastatin ), dose I (0.0225 g/200 gBW),dose II (0,045 g/200gWB), and dose III (0,09 g/200 gWB that was induced by highcholesterol diet for 14 days. Data is analyzed with One-Way Anovatest continued with LSD Post Hoc test. Results: phytochemical testresult shows garlic chives n-hexane extract containsteroid/terpenoid secondary metabolite. Statistical analysis showedsignificance difference between average cholesterol level fromcontrol group ( negative and positive ) against dose I group ,II anddose III group (p<0,05) at day-42. The effective dose was 0,045g/200 gWB. Conclusion: n-hexane extract of garlic chives has LDLreduction effect on albino male wistar rat with effective dose at0,045 g/200 gWB which shows the same activity with pravastatincontrol group. Keyword: Allium tuberosum Rottl ex Spreng, n-hexane extract of garlic chives, high cholesterol diet, total cholesterol level loweringeffect